Pathophysiology of Hyponatremia in Preterm Infants with Relative Adrenal Insufficiency after the Early Neonatal Period - Akita, Mitsuyo; Tomotaki, Seiichi; Hanaoka, Shintaro; Araki, Ryosuke; Motokura, Kouji; Tomobe, Yutaro; Tomotaki, Hiroko; Iwanaga, Kougoro; Takita, Junko; Kawai, Masahiko (American Journal of Perinatology, 2024)
Preterm infants often develop relative adrenal insufficiency (RAI) not only within the early neonatal period but also beyond this period. RAI is commonly accompanied by hyponatremia, but the pathogenesis of hyponatremia with RAI has not been clarified. This study aimed to investigate the pathophysiology of hyponatremia in infants with RAI.This is a single-centered retrospective cohort study. Preterm infants born at <30 weeks of gestation or birth weight <1,000 g were enrolled. They were divided into the RAI group and the non-RAI group. The data of serum and urine examination, the amount of sodium intake, and fractional excretion of sodium (FENa) were compared between the two groups. In the RAI group, data before and after the administration of hydrocortisone were also compared.Sixteen infants in the RAI group and 35 infants in the non-RAI group were included in the analysis. In the RAI group, hyponatremia was common and preceded other clinical symptoms, such as oliguria and decreased blood pressure, therefore, hyponatremia with RAI was not likely to be caused by dilution due to oliguria. There was no difference in the FENa between the two groups (adjusted for postconceptional age at examination), therefore, it is not likely that hyponatremia with RAI was mainly caused by excessive renal sodium loss. Since sodium intake was rather higher in the RAI group than in the non-RAI group, it is unlikely that insufficient sodium supplementation was the cause of RAI. Hyponatremia with RAI was considered to be likely caused by vascular hyperpermeability.Hyponatremia is a common symptom among preterm infants with RAI and its pathogenesis can be vascular hyperpermeability.
Keywords: hyponatremia; relative adrenal insufficiency; preterm; infant; sodium; vascular hyperpermeability; hydrocortisone